Upaya Penguatan Regulasi Untuk Mencegah Tindak Pidana Korupsi - Hariwangsa, Tridian; Henny Yuningsih (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
Corruption is a major problem that hinders the progress and stability of a country, including Indonesia. The entrenched practice of corruption in various sectors of government and social life not only undermines public trust but also causes significant losses for the country, both financially and socially. Not only the government should receive fair public services, but also ordinary people who feel the loss. The main challenge is poor inter-agency coordination, which leads to overlap and a lack of efficiency in handling corruption cases. Political interference that disrupts the independence of law enforcement agencies often causes investigations and prosecutions of corruption cases to be suboptimal. The deeply rooted culture of corruption complicates efforts to eradicate corruption. Corruption does not only occur at the level of high officials, but has also spread to lower levels within the government bureaucracy. Strengthening anti-corruption regulations is essential through better collaboration between the community and law enforcement agencies. Transparency in law enforcement and adequate protection for whistleblowers of corruption cases are also very important to encourage the public to be more courageous in reporting the corruption crimes they are aware of. To address this issue, active community participation and the enhancement of law enforcement agency capacities will be very important. With strong support from the government, strict regulations, and a good legal culture, the eradication of corruption in Indonesia can be more effective and have a positive impact on national development.